Examining unpaid care work of women in the sandwich generation pathways towards social protection and wellbeing - Tongson, Excelsa C. (2019)
Drawing from feminist standpoint epistemology and Kabeer's Social Relation Approach, this research is anchored on three critical points. First, it claims that women are authentic sources of knowledge that aid in the understanding of society. Second, it asserts that, as owners of their narratives, women in the sandwich generation bring along with them abundant and solid resources that contain both their dominant and subordinated views and persona in providing unpaid care. Lastly, it treats women's experiences not only as instruments for understanding how society operates but more importantly as dynamic vehicles for reorganizing and changing society's structure and workings. The situation of seven low-income urban women in the sandwich generation shows a major confluence of class, gender, age, and other identities. In terms of current policies, the single-determinant approach focusing only on one aspect of social protection has largely ignored individual differences and other identities this limiting our understanding of how the world of women in the sandwich generation revolves and functions around their triple roles.